Electrospun aligned PCLl/gelatin scaffolds mimicking the skin ECM for effective antimicrobial wound dressings - Ghomi, Erfan Rezvani (2023)
Bacterial infections and multidrug-resistant bacteria are major health burdens in wound care. Biocompatible antimicrobial agents, e.g., ε-polylysine (ε-PL), provide a broad spectrum of antibacterial properties and support dermal cell growth. Here, ε-PL was incorporated into polycaprolactone (PCL)/gelatin electrospun scaffolds collected at varying rotation speeds. Then, the samples were crosslinked using dopamine hydrochloride to provide highly proliferative dressings with broad antimicrobial activity. The morphological study showed that the electrospun wound dressings were smooth, continuous, and bead-free, with a mean diameter ranging from 267 ± 7 to 331 ± 8 nm for all random and aligned nanofibers. The fiber alignment of the electrospun PCL/gelatin scaffolds improved their tensile strength and modulus. Moreover, nanofiber mats are highly hydrophilic, which is crucial for an efficient wound dressing. The samples also demonstrated high antimicrobial properties against common wound bacterial strains, including methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus aureus (SA), Escherichia coli (EC), Acinetobacter baumannii (AB), and Pseudomonas aeruginosa (PA). Mammalian cell proliferation and morphology assays involving primary human dermal fibroblasts (hDFs) and immortalized keratinocytes (HaCaT) showed excellent biocompatibility of the electrospun mats and remarkably aligned mats. Furthermore, aligned mats showed more cell migration than randomly oriented mats, which is desirable for more efficient wound healing. Therefore, it can be concluded that aligned PCL/gelatin mats containing ε-PL are promising for potential use in wound dressings. Graphical Abstract: [Figure not available: see fulltext.].